Legalitas Kekuasaan Sultan Mahmud Badaruddin III - Habiburrahman Habiburrahman (Medina-te : Jurnal Studi Islam, 2016)
Sultanate of Palembang Darussalam is one of Sultanate in the Nusantara archipelago. The first Sultan of Palembang Darussalam, Susuhunan Abdurrahman was appointed as Sultan on March 3, 1666. In 1821 the Sultanate of Palembang are frozen by the Netherlands, and was resurrected again on March 3, 2003 by the Assembly of the Majelis Adat of Sultanate of Palembang Darussalam with its designation of Raden Sjafei Prabu Diradja,  as a Sultan of Palembang Darussalam with the title of Sultan Mahmud Badarudin III. Legality of power of Sultan Mahmud Power Badarudin III, referring to the basic characteristics of the legality of power in the Malay Islamic Sultanate system, base on very important factor as follows: first, direct descendant of former sultans of Palembang Darussalam Sultanate. Second, supported by the Ulama. Third, has an artifact that became a symbol of the sovereignty of the Sultanate of palembang darussalam belonging to former sultans. Regarding the form of the implementation of the legality of the power of the Sultan Mahmud Badaruddin III, that can be seen from the existence of activities, such as; the preparation of Dictionaries Baso Palembang, designation guguk-guguk inside and outside of Palembang, Attend different events and seminars related to the Sultanate of Palembang Darussalam, and maintaining continuity, customs, art and culture of the nation of Indonesia including environmental sustainability, particularly in the city of Palembang Darussalam.